Role of Different Integer Virtual Machine in Cloud Data Center - Arif Ullah; Nazri Mohd Nawi; Hairulnizam Bin Mahdin; Samad Baseer; Mustafa Mat Deris (Politeknik Negeri Padang, 2019)
In modern data centres of cloud computing contains virtualization system. In order to improve network stability, energy efficiency, and makespan proper virtualization need. The virtual machine is one of the examples of virtualizations. Cloud computing data centres consist of millions of virtual machine to manage load balancing. In this study check the different number of virtual machine role in data centres, for that purpose, we established a network with the help of cloudsim and compare different data centres at each zones taking a different number of the virtual machine with different paramater and network banwith.After the simulation the result shows that increasning in the number of VM can affect the netwok accuracy in term of energy ,processing time ,coast and network stabality .